A review on Cone Beam Computed Tomography in dentistry - Nimeshkumar Patel; Ekta Mistry (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2021)
Introduction: Cone Beam Computed Tomography (CBCT) has transformed the manner in which radiological evaluation is performed.  Methods: This article discusses the different aspects of CBCT, common dental applications of CBCT for diagnosis and treatment in different dental specialties from the current literature.  Results: CBCT has been widely accepted into different dental practices. The main reasons are the decreased size, low cost, less exposure to radiation as compared to computed tomography. CBCT enables the three dimensional assessment of the region of maxilla, mandible, cranium, and associated structures. Conclusions: Dentists and dental specialists can utilize three dimensional radiography- CBCT for a comprehensive diagnosis. CBCT can also help in identifying the structures such as root canals, bifurcated canals, supernumerary teeth, impacted teeth in different planes and thus are a valuable tool for dental treatment planning.